Profunda Femoris Pseudoaneurysm following Total Hip Arthroplasty Revision - Katharine Harper; Justin Iorio; Easwaran Balasubramanian (Case Reports in Orthopedics)
Vascular injuries following total hip arthroplasty (THA) are very rare, with pseudoaneurysm being a small subset. We report a case of profunda femoris artery (PFA) pseudoaneurysm in a 61-year-old male following a posterior approach revision left THA. Presentation involved continued blood transfusion requirements several weeks postoperatively. Diagnosis of the pseduoaneurysm was made by contrast CT of the lower extremity, with confirmation via IR angiography. Successful embolization was achieved with selective coiling and Gelfoam. Presenting complaints of such complications are often vague and therefore lead to delayed diagnosis. Causes of such complications are not completely understood, particularly with PFA injuries in THA. Possible mechanisms are discussed in this paper. Vascular complications following THA can be difficult to diagnose. High suspicion in the setting of continued postoperative pain or bleeding may allow prompt diagnosis and avoidance of serious limb-threatening complications.